Papers - literary, scientific, & c. - Jenkin, Fleeming, 1833-1885 (Longmans, Green, and Co., 1887)
These papers, each in its way representative, have been chosen for republication from amongst Fleeming Jenkin's technical writings. They include, in popular form, an account of the scientific development of submarine telegraphy, a work in which he took a large share during the earlier part of his professional life.